Quality by Design as a risk-based strategy in pharmaceutical analysis: Development of a liquid chromatography-tandem mass spectrometry method for the determination of nintedanib and its impurities - Pasquini, Benedetta; Orlandini, Serena; Furlanetto, Sandra; Gotti, Roberto; Del Bubba, Massimo; Boscaro, Francesca; Bertaccini, Bruno; Douša, Michal; Pieraccini, Giuseppe (Journal of chromatography. A, 2020)
Nintedanib (NIN) is a tyrosine kinase inhibitor recently approved for the treatment of idiopathic pulmonary fibrosis. As a new drug, no monograph is available so far in official compendia. A liquid chromatography-tandem mass spectrometry method is presented for the simultaneous determination of NIN and its seven potential impurities. The risk-based approach of Analytical Quality by Design was applied in method development. The critical method parameters (CMPs) were the type of organic solvent in the mobile phase, formic acid percentage, column flow rate, oven temperature, gradient slope of organic eluent. The critical method attributes (CMAs) were selected as analysis time and selectivity between the main compound NIN and the adjacent peaks. Design of Experiments methodology was effectively employed for establishing the relationship between the CMPs and the CMAs. In the scouting step, a Restek Ultra AQ C18 (100 × 2.1 mm, 2.7 µm) core-shell column was selected, and then the effects of different levels of the five CMPs on the CMAs were evaluated by means of a 35//16 symmetric screening matrix. A Box-Behnken Design made it possible to obtain detailed maps of predicted CMAs throughout the investigated experimental domain, pointing out the presence of interaction and quadratic effects. The probability of meeting the specifications for the CMAs was calculated by Monte-Carlo simulations, performing a risk analysis and drawing risk of failure maps, which were used to visualize and define the method operable design region (MODR) with a probability π ≥ 90%. The final working conditions (enclosing the MODR interval) were as follows: methanol as organic solvent; formic acid percentage, 0.15% v/v; flow rate, 0.40 mL min-1 (0.37-0.43 mL min-1); oven temperature, 40 °C (38-40 °C); gradient slope of organic eluent, 14.00% eluent B min-1 (12.85-15.15% eluent B min-1). The resulting analysis time was about 10 min. Validation was carried out according to International Council for Harmonisation guidelines and the optimized method was applied to the analysis of NIN soft capsules for quality control purposes.
Keywords: Chromatography, Liquid; Quality Control; řízení kvality; Solvents; indoly; rozpouštědla; tandemová hmotnostní spektrometrie; Impurities; Experimental design; Nintedanib; reprodukovatelnost výsledků; chromatografie kapalinová; Reproducibility of Results; LC-MS/MS; Monte Carlo Method; Indoles; metoda Monte Carlo; Risk; Method operable design region; Quality by Design; Tandem Mass Spectrometry; riziko; pravděpodobnost; Probability